Pandemi Covid-19 Terhadap Perkembangan dan Regenerasi Perwasitan Bulutangkis Indonesia - Saifullah Arif; Rifqi Arsyad; Helmi Yuhdana Haryanto (Journal of Physical Activity and Sports (JPAS), 2022)
The Covid-19 pandemic is a pandemic caused by the Coronavirus which has begun to infect almost the entire world since the beginning of 2020. This virus spreads rapidly and causes paralysis of activities in various sectors, such as the office, trade, entertainment and sports sectors. Some of the impacts of the virus are that many people are infected, deaths are everywhere, strict rules of health procedures, cessation of commercial and academic activities in schools, hospitals full of patients, and so on. One very significant impact is the prohibition of activities that create a crowd, for example, sports matches. As a result of the ban, all scheduled matches or events from all sports, including badminton. This has led to the sluggishness of the athletes in several badminton clubs throughout Indonesia. In addition, with the absence of badminton match activities, the development and regeneration of referees have been hampered. Referees who are experienced have to be on hiatus for a long time and referees who are just starting their careers are hampered in seeking experience. This is due to the absence of referee briefing activities, practice leading in the field, providing material, adding flight hours, and so on. For this reason, a study is needed to examine the effect of the Covid-19 pandemic on the development and regeneration of badminton refereeing in Indonesia. This study aims to find out what are the effects of the Covid-19 pandemic on the development and regeneration of badminton refereeing in Indonesia. This research includes a qualitative descriptive study that aims to explain the influence of Covid-19 on the development and regeneration of badminton referees who have been on hiatus for months. The research subjects were five PBSI Central Java provincial referees out of a total of 18 referees with various licenses ranging from provincial licenses to Asian badminton. The data collection method used in this research is the interview and observation method. The observation method is carried out by observing the conditions in the field and connected to the relevant context and theory. The interview method serves to determine the progress of the referee who did not appear when the observation method was carried out. The research outputs used are accredited national journals and literacy-based badminton sports teaching materials.